1971
DOI: 10.1002/1097-0142(197101)27:1<150::aid-cncr2820270123>3.0.co;2-0
|View full text |Cite
|
Sign up to set email alerts
|

Electron microscopic evidence suggesting the myogenous derivation of the so-called alveolar soft part sarcoma

Abstract: Electron microscopic study has revealed distinctly different granules in cells comprising alveolar soft part sarcoma, carotid body tumor (nonchromaffin paraganglioma), malignant melanoma, and granular cell myoblastoma which allow for their differential diagnosis. This, as well as other pertinent information, militate against views that implicate a histogenetic relationship between alveolar soft part sarcoma and anatomical analogues of these alveolated neoplasms or those of neutral origin. On the other hand, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
1

Year Published

1972
1972
2006
2006

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 99 publications
(17 citation statements)
references
References 13 publications
1
15
0
1
Order By: Relevance
“…10 12 23-25 The composition of these crystals was interpreted as a product similar to renin 24 or aggregates of actin filaments, 25 and it was suggested that they could be similar to the inclusions seen in rhabdomyoma or nemaline rod myopathy. 26 However, elegant recent work by Ladanyi et al, 27 including ultrastructural immunohistochemistry, has convincingly shown that the crystals consist of aggregates of the monocarboxylate transporter protein MCT1 and its cellular chaperone CD147. 27 …”
Section: Histopathological Featuresmentioning
confidence: 99%
See 1 more Smart Citation
“…10 12 23-25 The composition of these crystals was interpreted as a product similar to renin 24 or aggregates of actin filaments, 25 and it was suggested that they could be similar to the inclusions seen in rhabdomyoma or nemaline rod myopathy. 26 However, elegant recent work by Ladanyi et al, 27 including ultrastructural immunohistochemistry, has convincingly shown that the crystals consist of aggregates of the monocarboxylate transporter protein MCT1 and its cellular chaperone CD147. 27 …”
Section: Histopathological Featuresmentioning
confidence: 99%
“…25 61 Similarly, the suggestion that ASPSs were malignant angioreninomas has been disproved by negative immunohistochemical studies for renin, as well as by the absence of clinical signs of hyperreninism in patients with ASPS. 25 Perhaps the longest lived hypothesis has been that ASPS is an unusual myogenous tumour, on the basis of some ultrastructural similarity of a component of the ASPS crystal to actin filaments, 25 overlap between the appearance of these crystals and those seen in nemaline myopathy and rhabdomyoma, 26 and variable expression of muscle-related proteins, such as actins and desmin. 28 However, as discussed in the section Immunohistochemical findings, the specificity and significance of these immunohistochemical findings have been questioned, and there is no convincing evidence of expression of truly muscle-specific proteins in ASPS.…”
Section: Line Of Differentiationmentioning
confidence: 99%
“…Rare sites, such as the uterus, the mediastinum, and bones have also been described [14,34,38]. The majority of the pathologists dealing with this tumor tried to present evidence for its myogenic origin [3,7,13,15,16,19,27,30,31,32,36]. Some other "lines of differentiations" (paraganglioma, granular cell myoblastoma, neural neoplasm, and angioreninoma) -although only transiently -have also been raised in the literature [9,23,32].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous attempts have been made to define its tissue or cell origin. Ultrastructural analyses revealed the presence of the highly specific crystalloids, consisting of characteristically arranged actin filaments [3,13,31]. This fact raised the possibility of its muscle origin.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation